Frankliniella occidentalis (Thysanoptera: Thripidae) in spray-type carnations: spatial distribution analysis - Mateus, C.=700 1 Araujo, J.; Mexia, A.
(Es, En)
ilus., 20 ref.
Keywords: THYSANOPTERA; FRANKLINIELLA OCCIDENTALIS; DIANTHUS; DISTRIBUCION GEOGRAFICA; ESPAÑA; CLAVEL